A Drone-Based Parking Enforcement System Using Ardu Pilot and Raspberry Pi 4 - Mohamed Hafiz, Muhammad Hadi Syazwan; Zakaria, Mohamad Fauzi (Evolution in Electrical and Electronic Engineering, 2025)
Accelerated urbanization has exacerbated parking-related challenges in urban centers, as inadequate enforcement leads to congestion, increased fuel use, and environmental deterioration. Conventional enforcement techniques, dependent on manual inspection, are labor-intensive, prone to errors, and lack scalability. This study introduces an automated drone-based parking enforcement system utilizing a 3DR Quadrotor equipped with the ArduPilot Navio2 autopilot and a Raspberry Pi 4 onboard computer. The platform utilizes high-resolution image sensors for real-time vehicle identification and license plate recognition (LPR). Flight dynamics and navigation are regulated by ArduPilot firmware, whilst LPR algorithms implemented on the Raspberry Pi analyze collected photos. Identified license plate information is delivered by secure Wi-Fi to a cloud-based Node-RED interface for analysis, visualization, and enforcement measures. The suggested system seeks to provide an effective and scalable solution that guarantees precise detection, dependable data transfer, and autonomous functionality in open-area parking lots. Experimental validation confirms its capability to surpass the constraints of traditional approaches, providing enhanced accuracy, efficiency, and adaptability for smart city applications.